Enzymatic Insitu Crosslinking Can Improve Hydrogel Stability While Maintaining Matrix Stiffness - Kuth, Sonja; Boccaccini, Aldo R. (ChemistrySelect, 2024)
Next to the choice of a material, the crosslinking characteristics play an important role in the development of hydrogels for applications in the biomedical field. By decreasing crosslinking time or concentration one can reduce the density of the network and hence the stiffness of the hydrogel. However, at the same time in many cases the stability of the matrix is significantly reduced, leading to a rapidly degrading hydrogel structure. In this study, we evaluate and compare two different crosslinking methods while maintaining the material chemistry. The hydrogel system evaluated consisted of oxidized hyaluronic acid and gelatin, and it was crosslinked with microbial transglutaminase. We found that by in situ crosslinking (CL) instead of post CL we can significantly increase the stability of the hydrogel while maintaining the matrix stiffness. Encapsulated embryonic mouse fibroblasts showed an increased viability in in situ crosslinked samples. These findings indicate that it is possible to change hydrogel parameters independently, even if they are otherwise interrelated.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Enzymes; Hyaluronic acid; Hydrogel; Microbial transglutaminase; Oxidation